A Reduction in Pain Intensity Is More Strongly Associated With Improved Physical Functioning in Frustration Tolerant Individuals: A Longitudinal Moderation Study in Chronic Pain Patients - Suso-Ribera, Carlos; Camacho-Guerrero, Laura; Osma, Jorge; Suso-Vergara, Santiago; Gallardo-Pujol, David (Frontiers in Psychology, 2019)
Objective The onset and chronification of pain often has devastating consequences on the physical and mental functioning of individuals. Medical interventions are quite efficacious in reducing pain levels. However, changes in physical and mental health status after medical interventions are not proportional. In the past decades, rational/irrational beliefs, especially catastrophizing, have contributed to a better understanding of the pain experience. This study explores whether pain reduction efforts are more beneficial for individuals scoring high in rational thinking (moderation). Methods The study design was longitudinal. Patients were assessed twice, 2 weeks prior to the start of medical treatment at the pain clinic and 6 months after. A total of 163 patients with heterogeneous pain (mostly low back and neck pain) participated in the study. Their mean age was 58.74 years (SD = 14.28) and 61.3% were female. Results Overall, there was a reduction in pain intensity (t = 4.25, p < 0.001, d = 0.32). An improvement in physical functioning (t = 4.02, p < 0.001, d = 0.19), but not mental health (t = -0.66, p = 0.511, d = 0.11) was also observed. In the regression analyses, a decrease in pain intensity was moderately associated with improved physical health (β = 0.87, t = 4.96, p < 0.001, R2 change = 0.177). This association was found to be moderated by frustration tolerance (β = -0.49, t = -2.80, p = 0.006, R2 change = 0.039). Specifically, post hoc analyses indicated that changes in pain intensity only correlated with changes in physical health when patients reported high frustration tolerance levels (r = 0.47, p = 0.006, M = 7, n = 32), but not when patients were intolerant to frustration (r = 0.28, p = 0.078, M = 17, n = 41). Conclusion The results suggest that frustration tolerance may render adaptive by facilitating the positive effect that a reduction in pain intensity has on physical health status. The study findings are discussed in the context of personalized therapy with an emphasis on how to maximize the effectiveness of current interventions for pain.